Risk Assessment and Fitness Cost of Tetraniliprole Resistance in Ostrinia furnacalis (Lepidoptera: Crambidae) - Tingting Xu; Fei Hu; Ran Yue; Benjin Hu; Sijia Bi; Youmin Tong; Lina Xu (Agronomy)
Asian corn borer (ACB), Ostrinia furnacalis, is a predominant pest species that is widely distributed across major corn-growing regions in China. Tetraniliprole, a novel diamid insecticide, exhibited good efficacy on lepidopteran insect pests and was officially sanctioned for controlling ACB in China. In this study, a tetraniliprole-resistant strain called ACB-TLR was obtained from a susceptible strain, ACB-SS, after 10 continuous generation selections with tetraniliprole. Additionally, the fitness cost of the ACB-TLR strain was assessed. The results showed that ACB developed 11.58-fold resistance to tetraniliprole and the realized heritability was estimated as 0.213. The ACB-TLR strain displayed 2.10 times cross-resistance to chlorantraniliprole, but we found no cross-resistance to emamectin benzoate and deltamethrin. The development time of larvae and pupae was significantly prolonged, the adult longevity was significantly shorter, and the pupation and emergence rates were significantly reduced in the ACB-TLR strain than in the ACB-SS strain, with a relative fitness of 0.39. The current study indicated that ACB has the potential to develop resistance to tetraniliprole in the field. However, the decreased fitness may allow insecticide resistance to be managed.